Evaluating a Refined Technical Debt Management Framework in Long-Lived Agile Projects: A Mixed-Methods Case Study - Järvinen, Mikael (My University, 2026)
Long-lived Agile software projects accumulate technical debt (TD) under feature pressure. This thesis evaluates the practical applicability of a refined Technical Debt Management Framework (TDMF), developed from the author's bachelor's-thesis precursor, in an industrial Agile software development team. The research questions concern how the framework's proposed application works in practice, how team members perceive it, what benefits and challenges arise, and how it should be adapted. The study is a single-team, four-week mixed-methods case study at a Finnish software organisation maintaining a two-decade-old SaaS platform. Data were collected through a focus group, ten observed team meetings, five post-implementation interviews, and pre- and post-implementation Likert questionnaires. Qualitative data were analysed through reflexive thematic analysis; quantitative data were reported as group-level descriptive statistics. The framework was applied selectively. The team adopted its structural elements — a recurring TD discussion forum, allocated time, and consistent recording of TD items — at kick-off, but sustained enactment was partial under capacity pressure. The framework's calculative prioritisation step (ROI based on principal-and-interest estimates) was declined at the first refinement and not reinstated. The team identified the framework's most valuable potential as upward communication of TD to management — a register the framework did not address. Four adaptation directions are derived: upward-facing artefacts for management communication, presenting the calculative step as conditional rather than default, substrate-aware framing, and definitional conventions for TD measurement. The case study contributes evidence that calculative TDM steps require enabling conditions often absent in long-lived Agile projects, and identifies upward-facing communication as an underdeveloped leverage point for framework design.
Keywords: technical debt management; TDMF; Agile software development; Scrum; case study; reflexive thematic analysis; framework evaluation